A Qualitative Analysis on the Definition of Zakat in the Turkish Tax System and Institutionalization of Zakat - Mehmet Cural; Esra Berika Dönmez (Journal of Islamic Economics, 2025)
Few studies research about zakat and tax system in Türkiye. This research discusses the institutionalization of zakat in Türkiye and the tax advantages that could be provided for zakat payments. A qualitative method and semi-structured interviews are preferred in the research. Accordingly, interviews are conducted with 21 income taxpayers who pay zakat. Participants were asked about their definition of zakat, methods they use when giving zakat, their perspectives on the definition and institutionalization of zakat in the tax system and their thoughts on tax advantages that could be provided for zakat. The results show that 14 participants consider the institutionalization of zakat necessary. All participants emphasized that the institutional structure should ensure trust and transparency principles. 13 out of 21 participants stated that institutionalization should be done by the state, while 10 stated that a different system established by the state should be implemented. 5 participants expressed views against the institutionalization of zakat by the state. 12 participants expressed their desire for zakat to be defined in the Turkish tax system but expressed hesitation regarding the provision of tax advantages; 8 participants emphasized the necessity of providing tax advantages. As a result, it is thought that the institutionalization of zakat in Türkiye may reduce the impact of social transfer expenditures on the budget.